Vortex flow in the outlet duct of an axial compressor in the rotating stall regime - Teverovskii,MA; Chernyshenko,SI (Fluid Dynamics, 1998)
An ideal incompressible fluid flow in the right half-plane periodic in the transverse direction is considered. This flow models that in the outlet duct of an axial compressor in the rotating stall regime. It is a feature of the problem that in the inlet cross-section two velocity components are prescribed while the vorticity distribution is unknown. An explicit solution is found in the form of a series in a small parameter characterizing the deviation of the velocity from a constant value. Numerical results are obtained.